Enhanced neural differentiation of human‐induced pluripotent stem cells on aligned laminin‐functionalized polyethersulfone nanofibers; a comparison between aligned and random fibers on neurogenesis. Issue 3 (14th October 2021) - Ghollasi, Marzieh; Poormoghadam, Delaram
Abstract: Despite the numerous attempts in nerve tissue engineering, no ideal strategy has been translated into effective therapy for neuronal regeneration yet. Here, we designed a novel nerve regeneration scaffold combining aligned laminin‐immobilized polyethersulfone (PES) nanofibers and human‐induced pluripotent stem cells (hiPSCs) for transplantation strategies. Aligned and random PES nanofibers were fabricated by electrospinning method with a diameter of 95–500 nm and were then modified with covalent laminin bounding subsequent to O2 plasma treatment. PES‐functionalized fibers found to induce a remarkable higher rate of neuronal genes expression as compared to nontreated group. In addition, hiPSCs cultured on aligned pure fibers exhibited the extension of neurites along with fibers direction and an exponentially elevated expression of neuron specific enolase (early neuroectoderm marker), Tuj‐1 (axonal marker), and microtubule‐associated protein 2 (dendritic marker) in comparison with random pure fibers. The concomitant of increased hydrophilicity and biocompatibility along with exploiting topographical cues and directional guidance make aligned PES‐plasma‐laminin a versatile scaffold for adhesion, proliferation, spreading, and differentiation of hiPSCs into nerve cells. Abstract :